Pengaruh Word Of Mouth dan Atribut Produk Terhadap Keputusan Nasabah Bank Muamalat Kcp Ponorogo Menggunakan Kartu Shar-E Debit Reguler GPN - Fuatqi, Faruq Ahmad; Pertiwi, Puspita Candra (JAPP: JURNAL AKUNTANSI, PERPAJAKAN DAN PORTOFOLIO, 2023)
In modern times there are still companies that use traditional promotion concepts, one of which is Bank Muamalat KCP Ponorogo which still prioritizes promotion through word of mouth / word of mouth communication, even though in the modern era like today promotions through social media such as Instagram, web, pamphlets and so on that are in great demand and widely used by other companies. In addition, the product attributes on the GPN Regular Shar-E Debit card are still not in accordance with the product attribute theory where there are often problems when used and the card often has errors. However, savings customers using the Regular GPN Shar-e Debit card product at Bank Muamalat KCP Ponorogo continued to increase.The purpose of this study was to determine and analyze the effect of word of mouth and product attributes on purchasing decisions for the Shar-E Debit Regular GPN card product for savings customers at Bank Muamalat KCP Ponorogo.Based on the results of the analysis concluded, word of mouth communication does not significantly affect purchasing decisions, while product attributes have a significant effect on purchasing decisions. However, word of mouth communication and product attributes together have an effect on purchasing decisions.